Design, development, and scientific performance of the Raman Laser Spectrometer EQM on the 2020 ExoMars (ESA) Mission. (29th September 2019) - Moral, Andoni G.; Rull, Fernando; Maurice, Sylvestre; Hutchinson, Ian B.; Canora, Carlos P.; Seoane, Laura; López‐Reyes, Guillermo; Rodriguez Prieto, Jose A.; Rodríguez, Pablo; Ramos, Gonzalo; Parot, Yann; Forni, Olivier
Abstract: The Raman Laser Spectrometer (RLS) is one of the three Pasteur Payload instruments located within the rover analytical laboratory drawer (ALD), for ESA's Aurora exploration programme, ExoMars 2020 mission. The instrument will analyse the crushed surface and subsurface samples that are positioned below the Raman optical head by the ALD carousel. The RLS engineering and qualification model (EQM) was delivered to ESA at the end of 2017, after a wide technical and scientific test characterization campaign. The scientific campaign comprised instrument calibration and detailed evaluation of the scientific requirements and overall performance. For spectral calibration, continuous emission standard lamps (such as Hg‐Ar, Ne, and Xe) were utilized, as well as Raman spectra of pure liquids typically used as standards (cyclohexane and carbon tetrachloride (CCl4 )). In addition, Raman spectra of the RLS calibration target (CT), a small disc of polyethylene terephthalate (PET) were obtained at various temperatures. This target, placed inside the rover, will be used for both Instrument health checks and calibration activities throughout Mars operations. For the scientific requirements and performance evaluations, several liquid and solid samples were analysed under a wide range of ambient conditions. The obtained spectral band parameters (peak position, relative peak intensity, peak width, and peak profile) were evaluated. Also, the instrument response (in terms of SNR) was characterized at different integration times and detector operating temperatures. In this paper, we provide a description of the development, verification, functional test, and overall scientific performance of the RLS instrument developed for ExoMars. Particular attention is placed on the performance of the EQM, which is the most representative instrument, in terms of engineering and functionality, of the flight model (FM) and in addition is used for performing all the mechanical, thermal, and radiation tests necessary for space qualification (for planetary applications). The data presented and analysed here, comprise part of the overall dataset obtained during the full instrument characterization campaign conducted at INTA before and during delivery and integration of the EQM in the rover ALD at TAS‐I facilities (Torino, Italy). The results obtained confirm that the full functionality and scientific performance of the RLS instrument was maintained after integration. Abstract : The Raman Laser Spectrometer (RLS) is one Payload instruments located within the Rover for the ESA's Aurora Exploration Programme, ExoMars 2020 mission. It will analyse Mars surface and sub‐surface samples. Obtained band parameters (spectrum peak position, relative peak intensity, peak width, and profile shape) were evaluated; and also the instrument response (in terms of SNR), at different integration times and detector operating temperatures, was characterized.